(untitled) (De la Crítica, 2025)
The integration of English as a cross-cutting element in higher education responds to the need to prepare students for a globalized and competitive world, where proficiency in this language facilitates access to up-to-date information, participation in international academic networks, and the development of specialized professional skills. In this regard, the objective of this essay is to explore the integration of English as a cross-curricular axis in interdisciplinary projects and its possible research applicability from a qualitative-interpretative perspective. To achieve this, a documentary research was conducted through the reading and selection of relevant studies on the topic, allowing for the identification of associated benefits, challenges, and methodological approaches. As a final consideration, it is concluded that the effective integration of English requires clear institutional policies, adequate teacher training, and sufficient resources, as only in this way can higher education become inclusive, contextualized, and aligned with the demands of the global market and the knowledge society.